Microvascular Changes Associated with Optic Disc Drusen: Case Report - Özlem Biçer (Türk Oftalmoloji Dergisi, 2019)

(untitled)
Optic disc drusen (ODD) is an important clinical entity that is sometimes misdiagnosed as papilledema because of elevated and blurred disc margins. A 17-year-old male who presented with headaches underwent detailed ophthalmological examination as well as colored fundus photography, B-scan ultrasonography (USG), fundus autofluorescence (FAF), optical coherence tomography (OCT), optical coherence tomography angiography (OCTA), and visual field testing. His visual acuity was 10/10 in both eyes. Fundus examination revealed bilateral blurred and elevated optic disc margins. Diagnosis of bilateral ODD was confirmed with B-scan USG. FAF imaging revealed hyperautofluorescent areas on both optic discs. Optic nerve head OCT scans showed elevated irregular disc borders and thinning of the retinal nerve fiber layer in both eyes. On visual field testing, loss of the nasal visual field was detected in the left eye. OCTA imaging showed focal capillary dropout, especially in the nasal peripapillary area, in both eyes and reduced peripapillary and macular vessel density. In this case report, we evaluated the clinical findings and the structural features of bilateral ODD with multimodal imaging modalities including OCTA.